O impacto da pandemia no ensino-aprendizagem no curso de Licenciatura em Ciências: Biologia e Química do IEAA - Rocha, Sthefanie Felix da (Brasil, 2022)
It is known that the pandemic has been modifying several sectors of society, whether in the economic, social, political and even educational issue, which leads us to rethink and remodel many daily activities, fulfilling many requirements such as social distancing, being a way to prevent against the spread of the virus. Within this perspective, in terms of the educational context, educational institutions have implemented remote teaching as a way to continue academic activities, leading us to think about the real impacts that this teaching medium has on the teaching-learning process. Given this scenario, this research sought to analyze the conception of students of the Science course: Biology and Chemistry on the main impacts that the pandemic has been causing in the teaching and learning process, based on the experience with remote teaching. The respective analysis was carried out based on a qualitative research, in which the online questionnaire was used as a data collection technique through the Google Forms platform, having as subjects involved the students enrolled and not dropping out of the Degree in Sciences: Biology and Chemistry, during the periods in which the institution worked with remote learning. The present study demonstrates the main impacts that this process causes on teaching and learning. The results point out questions about the conditions in relation to the personal organization of the participants, whether in the process of autonomy in carrying out the studies, of the skills in relation to the use of digital resources, as well as in certain difficulties faced such as the infeasibility of access to the internet network. , the non-access of all students in synchronous classes, some points being highlighted. However, it is necessary to reflect more and more on how remote teaching interfered in the process of training students in times of a pandemic. And thus, provide better conditions of access, from public policies so that it serves the entire academic community.